Exploring antecedents of destination brand engagement of tourists: The roles of destination brand experience and destination brand authenticity. (International Journal of Scientific Research and Management (IJSRM), 2024)
Research on destination brand engagement (DBE) within the tourism context has mainly focused on its outcomes rather than its antecedents. This study diverges from previous investigations to examine the impact of destination-focused drivers and a tourist-centric perspective on DBE. Specifically, the study explores how destination brand experience and destination brand authenticity (DBA) influence DBE. Results obtained from a sample of 530 tourists and tested using structural equation modeling techniques reveal that destination brand experience and DBA positively and significantly influence DBE. Finally, theoretical and significant managerial implications are discussed.